EFEKTIVITAS PROBLEM BASED LEARNING DAN PROJECT BASED LEARNING DITINJAU DARI KETERAMPILAN BERPIKIR KRITIS SISWA SD - Retno Triningsih; Mawardi Mawardi (JRPD (Jurnal Riset Pendidikan Dasar), 2020)
The purpose of conducting this research is to compare the effectiveness of the Problem Based Learning learning model and the Project Based Learning learning model in terms of the critical thinking skills of elementary students. This type of research used in this research is Quasi Experimental with experimental design of Post test-Only Control Group Design. The population in the study were 164 five grade students in Diponegoro Salatiga Cluster, while the sample is 111 students of five grade students in SDN Mangunsari 01, SDN Mangunsari 03, and SDN Mangunsari 05. The results obtained from this study are based on descriptive statistics where the average implementation of the Problem Based Learning learning model is 92.46, while the average implementation of the Project Based Learning learning model is 85.15. the results of critical thinking skills in the Problem Based Learning model are higher than the Project Based Learning learning model reinforced by the T test results obtained by the Sig. (2-tailed) of 0, 047 0.05 thus there is a significant difference between the two groups.